Analisis kausalitas pertumbuhan ekonomi terhadap ketimpangan distribusi pendapatan di Indonesia (1999-2019) Granger Causality - Rizky Enggar Wishartama; Zulgani Zulgani; Rosmeli Rosmeli (Konsentrasi Pembangunan Regional dan Publik, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2022)
The theory of economic growth states that an increase in economic growth will increase per capita income, decrease inequality in income distribution, and will have an impact on reducing the number of poor people, but an increase in economic growth also has an impact on an increase in the poor population, and an increase in income distribution inequality. So that the purpose of this study is to analyze the causality of economic growth and inequality of income distribution in Indonesia. The data that will be used in this research is secondary data which is time series from 1998-2019 obtained from the World Bank and the Central Bureau of Statistics. The analysis model used is the Granger Causality Test analysis. The variables that will be used in this research are GDP Indonesian at constant prices and the Gini ratio. Based on the results of this study, the development of Indonesia's gross domestic product based on the results of the Granger causality tends to affect the Gini Rato variable longer than the other way around.